Electrocatalytic activity of high-entropy alloys toward oxygen evolution reaction. (9th July 2018) - Cui, Xiaodan; Zhang, Boliang; Zeng, Congyuan; Guo, Shengmin
Abstract: Abstract : Due to the special crystal structures and electron configurations, high-entropy alloys (HEAs) are expected to have favorable activities for electrocatalytic reactions. In this paper, a set of oxygen evolution reaction (OER) criteria are applied for the HEA-based electrocatalyst design. Specifically, FeNiMnCrCu HEA is predicted to have a better OER performance than the baseline FeCoNiCrAl HEA. To demonstrate this design approach, both FeNiMnCrCu and FeCoNiCrAl samples are prepared and tested. Their crystal structures and electrocatalytic performance are examined. This paper demonstrates the potential of using finely tuned HEAs for OER applications.